Pediatric cancer research trends and performance in Africa: A bibliometric analysis from 1991 to 2022 - Moawia Mohammed Ali Elhassan; Ibrahim Mahmoud; Ibrahim Qaddoumi; Verna Vanderpuye; Jeannette Parkes; Yuh-Shan Ho (Elsevier, 2024)
Background: Childhood cancer rates in Africa are lower than in high-income countries but increasing, making pediatric cancers a significant public health concern. The purpose of this study was to provide an overview of the publication of pediatric cancer research in Africa, including publication types and citation trends over time. Methods: The Science Citation Index Expanded database within the Web of Science Core Collection was searched for articles published from 1991 to 2022 in the topic domain, using title, abstract, author keywords, and KeyWords Plus. Indicators used to assess publications performance of the countries included: total number of publications, single-country publications, collaborative publications with African countries, collaborative publications with non-African countries, first-author publications, corresponding-author publications, and single-author publications. Results: A total of 4461 relevant documents were retrieved, with 2770 original research articles. Annual number of articles rose from 13 articles in 1991 to 287 in 2022. Most articles were produced by Egypt (28 %) in North Africa, followed by South Africa (20 %) in sub-Saharan Africa. Collaboration between African countries remains low; however, international collaborations have enhanced the average number of citations per article. Most of the first authors (65 %) and corresponding authors (67 %) of these international collaborative articles were affiliated with non-African institutions. Conclusions: The number of publications sharply increased over the study period and diversely represents African countries. Collaborations with international partners increased citations; however, few of these publications had African first authors. Conversely, inter-institutional partnerships between African countries were relatively low, highlighting the need for better collaboration within Africa.